Elderly widows: from the loss to the reorganization - Suzuki, Milena Yuri (2013)
Widowhood is a phenomenon that affects mainly elderly women, one explanation for this fact is the greater longevity compared to the males, the loss causes feelings of grief and sadness and several transitions in people's lives, forces them facing transition of identity, loss of status and socioeconomic independence. Therefore, it is essential to understand the grieving process and coping strategies for mourning elaboration.